Ezoteryka a coaching, czyli współczesny rozwój osobisty w kontekście korzeni „wiedzy tajemnej” - Łagosz, Zbigniew (Humaniora. Czasopismo Internetowe, 2023)
This article attempts to portray the roots of coaching through the prism of esotericism, New Age, and occultism. The history of contemporary coaching is only coincidentally related to the emergence of New Age ideas and people who have influenced both systems. Using the example of the Polish coaching offer, the author demonstrates its similarities to esoteric and occult semantic and theoretical ideas.